Congenital alveolar rhabdomyosarcoma - case report - Sherief, Sadik Taju; Taye, Kalekirstos (International Journal of Clinical and Experimental Ophthalmology, 2022)
Rhabdomyosarcoma is the most common soft tissue sarcoma of childhood and is very rare in the neonatal period. At this age, the alveolar type is a remarkably uncommon variety. We report a 56 days old female with alveolar RMS of the right eye noted since the age of 7 days with fast progression and unfavorable prognosis. Congenital alveolar RMS is an important cause of neonatal onset rapidly progressive proptosis. Early onset, alveolar type, and late diagnosis were poor prognostic factor.